Treatment’s related predictors settings and relation to substitution fluid volume and dialysis dose on patients under On-Line Haemodifiltration - Fazendeiro, J.; Peralta, R.; Pinto, B.; Félix, C.; Carvalho, H.; Ponce, P. (54th ERA?EDTA Congress, 2017)
Introduction: Convective therapies are increasingly used in patients with end-stage kidney disease, augmenting the clearance of middle molecular weight uremic toxins, such as ?2 microglobulin, thus possibly improving patient outcomes. Haemodiafiltration by combining diffusive and convective transport, apparently significant decreases mortality risk in patients with high Substitution volume (SubsVol). Also, an adequate dialysis dose is one of the most import targets and should be ensured that patients receive the optimal treatment. Nonetheless, literature showed that treatment related factors, such as fixed treatment times (TT) and blood flow rates (BFR), rather than patient characteristics seems to have more influence on the magnitude of the convection volume. Objectives: To determine which factors explain the variation of spKt/V and substitution volume (SubsVol) in patients undergoing Online Haemodiafiltration (OL HDF). Methods: A multicentre, descriptive-correlational, observational study involving all active patients undergoing OL post-dilution HDF in multiple dialysis clinics. Data were collected for one month (April 2016) of follow-up. Only patients with internal vascular access were eligible. All dialysis machines used were from the same model and the dialysers had the same characteristics and area. Demographics data and various clinical treatment and laboratory parameters were collected. The backward elimination approach was used to select the best set of independent variables. The factors that contributed signi?cantly on influencing spKt/Vurea and SubsVol, were identified by regression analysis. Results were considered statistically significant when p< 0.05. Results: 2,829 patients were enrolled, the baseline characteristics were, age 68.96 SD=13.75 years, 60.8% were men. The average dry weight was 68.55 kg, UF removed 2.56 L, BFR 427.13 mL/min, TT 241.55 min, heparin dose was 58.15 UI/Kg, Haematocrit (vol%) 33.92, Overhydration (OH) status 1.53 L. The results for the dependents variables were, SubsVol 24.14 SD=2.60L and spKt/Vurea 2.05 SD=0.38. By the analysis of the results we considered a positive correlation r=0.688 and r=0.664 between factors for spKt/Vurea and SubsVol respectively. The multivariable regression analyses model was statistically significant [F (7, 2767) = 355.300, p <0.001] and explains 47.2% of the variation in spKt/V. Similar results were obtained for the SubsVol. As depicted in table 1 and table 2, the model showed that BFR, OH status and TT had a positive effect (statistically significant) on spKt/Vurea and SubsVol. Conclusions The factors with larger dimension of its negative effect on the dependent variables were dry weight (29.93%) and UF removed (18.19%). Oppositely it was concluded that the BFR was the factor with the greatest positive effect (28.13%). Anticoagulant dose doesn’t significantly explain spKt/V but is important for SubsVol, probably by counteracting the propensity for intradialyser clotting.